Anglicisms in French and their translation (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
English, being one of the most spoken languages in the world, is influenced by other languages in recent years, more and more. English borrowings are used in almost all languages. A large number of anglicisms "entered" in French language. They can be easily found in the French explanatory dictionary with transcriptions and definitions. The article is devoted to the topical issue of translation the anglicisms into French.
Keywords: anglicisms; borrowing; token; semantic loan translation; derivation; language-recipient